2024
DOI: 10.1021/acsmaterialslett.3c01401
|View full text |Cite
|
Sign up to set email alerts
|

Fabricating Covalent–Organic Quantum Dots through Selective Disassembly of Hydrogen-Covalent Hybridized Organic Frameworks for Efficient and Sensitive Uranium Detection

Zhimin Jia,
Xiaofeng Li,
Lei Su
et al.

Abstract: The preparation of low-dimensional covalent–organic frameworks (COFs) is currently a hot and challenging research topic, especially for zero-dimensional (0D) COF quantum dots (COQDs). Herein, for the first time we introduce a facile and efficient approach to fabricating COQDs by selectively disassembling hydrogen-covalent hybridized organic frameworks (H–COFs). By taking advantage of the disparate stabilities between noncovalent and covalent bonds within the periodic lamellar structures of H–COFs, we disrupt t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
0
0
Order By: Relevance
“…[21] Jia et al reported the preparation of fluorescent zero-dimensional COF quantum dots (QDs) and the application in low-concentration UO 2 2 + detection. [22] Wang and his team reported the preparation of red fluorescent nickel-doped self-assembled Cu nanoclusters and their application in detecting biological thiols. [23] Wang et al successfully synthesized SQDs in multiple colors and utilized them for applications in cell imaging, LED sensing, and other relevant fields.…”
Section: Introductionmentioning
confidence: 99%
“…[21] Jia et al reported the preparation of fluorescent zero-dimensional COF quantum dots (QDs) and the application in low-concentration UO 2 2 + detection. [22] Wang and his team reported the preparation of red fluorescent nickel-doped self-assembled Cu nanoclusters and their application in detecting biological thiols. [23] Wang et al successfully synthesized SQDs in multiple colors and utilized them for applications in cell imaging, LED sensing, and other relevant fields.…”
Section: Introductionmentioning
confidence: 99%